The Effectiveness of the Use of Village Funds in Infrastructure Development in Malomba Village, Dondo District, Tolitoli Regency: Efektivitas Penggunaan Dana Desa dalam Pembangunan Infrastruktur di Desa Malomba, Kecamatan Dondo, Kabupaten Tolitoli - Muh. Arif; Masri Arfandi (STIE MUJAHIDIN TOLITOLI, 2025)
The purpose of this study is to determine the Effectiveness of the Use of Village Funds in Infrastructure Development. This research includes qualitative research with studies that examine the effectiveness of village funds. The research produces descriptive data in the form of written or spoken words from people and observed behaviors. The data collection method in this study is the interview method. The results of the research on the effectiveness of the use of village funds in Malomba Village in the process of using the Village Fund for infrastructure development consist of three stages, namely planning, planning and supervision. From these stages, the effectiveness of the use of Village Funds in infrastructure development in Malomba Village, Dondo District, Tolitoli Regency. From the results of the research, it can be said that it has been effective.